Role of hypothalamic-pituitary-adrenal axis and catecholamine factors in independent and primary multiple types of tumor growth - E. M. Frantsiyants; V. A. Bandovkina; I. V. Kaplieva; E. I. Surikova; Yu. A. Pogorelova; N. D. Cheryarina; L. K. Trepitaki; I. V. Neskubina; A. A. Vereskunova; I. M. Kotieva; K. A. Shumarin; A. I. Shikhlyarova; et al. (Исследования и практика в медицине, 2022)
Purpose of the study. To study the levels of adrenal axis factors in the hypothalamus, adrenal glands, blood serum of mice and catecholamines in the adrenal glands during the independent growth of B16 melanoma and Lewis lung carcinoma (LLC) and their combined growth in female mice, and in males – with independent growth of B16 and combined growth of B16 and LLC.Materials and methods. Male and female BALB/c Nude mice were divided into groups, n = 7 each: group 1 involved intact animals, group 2 involved mice with B16/F10 melanoma, group 3 – mice with LLC, group 4 – synchronous growth of melanoma and LLC. Levels of corticotropin releasing, noradrenaline and dopamine were determined in homogenates of the hypothalamus and adrenal glands and in the blood serum of all animals by ELISA, and levels of 17‑hydroxyprogesterone (17-OHP), dehydroepiandrosterone sulfate (DHEA-S) and cortisol were determined by RIA. Statistical processing of results was performed using the Statistica 10.0 program.Results. All tumor-bearing females showed elevated corticotropin releasing in the hypothalamus together with an increase of all stress-characterizing parameters: cortisol, the cortisol/DHEA-S ratio, and noradrenaline. However, an increase in serum levels of cortisol was blocked by high levels of DHEA-S, and as a result, the cortisol/DHEA-S ratio was either within the normal range (B16 melanoma and B16+LLC combination) or reduced (LLC). Levels of corticotropin releasing in the hypothalamus of tumor-bearing males decreased, together with opposite changes in stress-characterizing parameters in the adrenal glands: cortisol increased, the cortisol/DHEA-S ratio did not differ significantly from the control values, and noradrenaline decreased. An increase in serum levels of cortisol was not blocked by high levels of DHEA-S, and as a result, the cortisol/DHEA-S ratio was sharply elevated in B16 melanoma and B16+LLC combination.Conclusion. At independent and primary multiple types of tumor growth, the sex-specific features of the functioning of the adrenal axis at the central and peripheral levels are observed, which determines a more pronounced stressful state of the body with B16+LLC combination growth, realized by various mechanisms.